How federal agencies can effectively manage records created using new social media tools / Azra Hannani Adni - Adni, Azra Hannani (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
The Obama administration has increased its use of Web 2.0 social media platforms to connect with individuals and engage them with government since taking office in January 2009. Numerous agencies have established social media teams and are keen to test out well-known commercial platforms like Twitter, Facebook, and YouTube. This has, produced a conundrum with regard to adherence to federal regulations governing the preservation and storage of official government records. In fact, this conundrum has made some organizations reluctant to fully embrace the social media revolution. So that, The numerous problems that this study identifies are not all resolved. However, it is a helpful manual for federal managers looking to engage citizens on social media while also adhering to the law's need to keep historical records for future generations. The report's recommendations for action and key insights are widely applicable.